Geographical Distribution of Methanogenic Archaea in Nine Representative Paddy Soils in China - Zu, Qianhui; Zhong, Linghao; Deng, Ye; Shi, Yu; Wang, Baozhan; Jia, Zhongjun; Lin, Xiangui; Feng, Youzhi (Frontiers in Microbiology, 2016)
Paddy field methanogenic archaea are responsible for methane (CH4) production and contribute significantly to climate change. The information regarding the spatial variations in the abundance, the diversity and the composition of such ecologically important microbes, however, is quite limited at large scale. In this investigation, we studied the abundance, alpha diversity and geographical distribution of methanogenic archaeal communities in nine representative paddy sites, along a large latitudinal gradient in China, using pyrosequencing and real-time quantitative PCR. It is found that all paddy soils harbor constant methanogenic archaeal constituents, which is dominated by family Methanocellaceae (37.3%), Methanobacteriaceae (22.1%), Methanosaetaceae (17.2%) and Methanosarcinaceae (9.8%). Methanogenic archaeal abundance is primarily influenced by soil C (R=0.612, P=0.001) and N (R=0.673, P=0.001) contents, as well as alpha diversity by soil pH (PD: R=-0.552, P=0.006; Chao1: R=-0.615, P=0.002). Further exploration revealed that both spatial distance (R=0.3469, P=0.001, partial mental test) and soil chemical variables mainly about soil C and N (R=0.2847, P=0.001) are the two major factors affecting methanogenic archaeal community composition distribution in paddy soils. This finding will allow us to develop a better picture of the biogeographic ranges of these ecologically important microbes and get deeper insights into their ecology.